Coastal exotic plant serves as a habitat for a notorious wetland pest in unfavorable seasons: A case study of exotic Spartina alterniflora in China - Xu, Tianping; Ma, Xu; Li, Yunjing; Xue, Hao; Zhao, Shilin; Liu, Zezheng (Frontiers in Marine Science, 2024)
Coastal biological invasions pose a wide-reaching threat to various ecosystems, affecting both vegetation and herbivores in native communities. Although herbivores often exert strong top-down control on vegetation, the impact of invasive species on consumers that strongly regulate native species in invaded ecosystems remains unclear. Therefore, through field surveys and feeding preference experiments, this study examined the effects of the invasive Spartina alterniflora Loisel. (hereafter, Spartina) on the native moth Laelia coenosa Hübner (hereafter, Laelia), a notorious pest that has been documented to cause significant damage to native Phragmites australis (Cav.) Trin. ex Steud. (hereafter, Phragmites) marshes in coastal wetlands of China. Field surveys showed that Laelia larvae were more abundant and had higher grazing rates in Phragmites than in Spartina marshes in summer, but these patterns reversed in autumn. Feeding experiments consistently showed that the dietary preference of Laelia larvae switched from Phragmites in summer to Spartina in autumn, likely because Spartina has a longer growing season and relatively higher nutritional quality than Phragmites in autumn. Thus, by providing shelters (i.e., dietary sources and habitats) during unfavorable seasons, Spartina invasions may facilitate this insect pest Laelia and potentially amplify its damage to native wetland vegetation. Our work reveals a novel, indirect mechanism of coastal invasion impacts and highlights the importance of incorporating seasonal variation in plant-herbivore interactions.